An examination of educator multicultural attitudes before and after a diversity dinner dialogue. Issue 1 (8th March 2021) - Merlin-Knoblich, Clare; Dameron, Merry Leigh
Abstract : Purpose: The demographic make-up of students in US public schools is becoming increasingly diverse, and a need exists to train teachers in multicultural competence. Despite this need, little research addresses multicultural competence training for in-service teachers. In this pilot study, we aimed to implement an intervention, known as a diversity dinner dialogue (DDD), in which elementary and university educators read the same diversity-related book, then gathered over dinner to discuss the book and its implications in their work. Design/methodology/approach: This study used a pre-experimental study and measured participants' reactions to the intervention, as well as changes in multicultural attitudes immediately and six months after the training. Findings: Findings indicated that participants had positive reactions to the DDD, yet multicultural attitudes decreased after the training, a potential indication that participants encountered racial identity development processes during the intervention. Research limitations/implications: Further research is needed on DDDs and interventions affecting educator multicultural attitudes in K-12 schools and higher education. Originality/value: This study contributes a new potential intervention for use in K-12 school and university partnerships that may support the development of culturally responsive teaching practices and catalyze participant experiences in racial identity development processes.